Blockchain Technology's Potential Applications in Human Resource of IT Sector (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Blockchain technology is now widely used across many industries, thanks to the advancement of science and technology and the changing times. The employment scenario in the work market has been worse recently due to the increase in social competition. Employers can increase productivity and reduce resource costs by implementing blockchain technology into human resource. Thus, human resource development has made extensive use of blockchain technology. The future potential applications of blockchain technology in HRD will be examined and researched in greater detail in this article.